Prospects for real estate development in Ukraine - RADKEVICH, Anatoliy; TKACH, Taisiia; BORODIN, Maksym; STRYZHAK, Semen (Ways to Improve Construction Efficiency, 2025)
The article analyzes the current prospects for real estate development in Ukraine, taking into account global digitalization trends and the challenges of post-war recovery. The main focus is on the need to transform traditional development models by implementing innovative digital solutions, such as Building Information Modeling (BIM), artificial intelligence (AI), the Internet of Things (IoT), and automated project management systems. It was determined that the industry remains fragmented, with a low level of digital integration, which hinders the efficiency of investment and construction processes, especially in the context of providing citizens with affordable housing. The problem statement is the need for a comprehensive approach to the modernization of development projects, taking into account both technical and social aspects, in particular, environmental sustainability and investment transparency. The study analyzes the main barriers that hinder digital transformation, including an insufficient legislative framework, a lack of digital specialists, and a low level of investor confidence in the latest technologies. A comparative analysis of Ukrainian and European experience in digital development was conducted, and the strengths and weaknesses of each model were identified. Based on the results obtained, a conceptual structural model of a digital development project was developed, which includes the stages of planning, resource management, implementation monitoring, and post-project analysis using digital tools. It is concluded that the implementation of digital technologies can significantly increase the efficiency, adaptability, and environmental responsibility of development projects. In particular, the proposed autonomous management model allows for reducing project implementation times, reducing costs, and improving the quality of the housing stock.